Two new species of feather mites (Acariformes, Astigmata) from the black-tailed godwit, Limosa limosa (Charadriiformes, Scolopacidae), in Korea - Han, Yeong-Deok; Mironov, Sergey V.; Min, Gi-Sik (PLoS ONE, 2022)
Two new species of feather mites are described from two individuals of the black-tailed godwit, Limosa limosa (Linnaeus, 1758), in Korea: Alloptes (Conuralloptes) neolimosae sp. nov. (Analgoidea, Alloptidae) and Phyllochaeta limosae sp. nov. (Pterolichoidea, Syringobiidae). Males of A. (C.) neolimosae sp. nov. are distinguished from A. (C.) limosae in having the hysteronotal shield with a straight anterior margin, setae h2 enlarged and slightly flattened in the basal half, and the terminal lamella monotonously transparent without sclerotized patches; females differ in having legs IV with ambulacral discs extending to or slightly beyond the level of setae f2. The discovery of P. limosae sp. nov. represents the first record of the feather mite genus Phyllochaeta on godwits of the genus Limosa Brisson, 1760 (Scolopacidae, Limosinae). Males of P. limosae sp. nov. are distinguished from P. secunda in having the terminal cleft semi-ovoid with a length-to-width ratio of 1.7, and the terminal membranes with 15 or 16 finger-shaped denticles; females differ in having the hysteronotal shield bearing faint longitudinal striations in the posterior third and lacking lacunae, and setae c1 situated posterior to the level of setae c2. Additionally, we obtained partial sequences of the mitochondrial cytochrome c oxidase subunit I (COI) gene from A. (C.) neolimosae sp. nov. and estimated genetic distances from 10 other Alloptes species based on comparisons of COI sequences.